Design method and preparation method of ZnSe substrate 2-5.5 [mu] m high-transmittance film
By designing and preparing a 2-5.5μm high-permeability film of ZnSe substrate, using film stack formula and film design software to optimize the film layer thickness, the performance problems of the existing ZnSe substrate film under different application ends and multi-environmental conditions are solved, and the performance problems of the existing ZnSe substrate films are achieved. High transmittance and stable performance under multiple conditions.
Patent Information
- Application Number
- CN202411530072.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-30
AI Technical Summary
The existing ZnSe substrate 2-5.5μm band anti-reverse film has high durability requirements at different application ends and is difficult to meet the performance requirements under various environmental conditions.
A design method and preparation method for a 2-5.5μm high-permeability film of ZnSe substrate was designed. The film layer thickness was optimized through the film stack formula and film design software to form Sub/YbF3/ZnSe/YbF3/ZnSe/YbF3/Y2O3/Al2O3/ The film layer structure of Air ensures the transmittance and durability requirements of the film system in the 2-5.5μm band.
It achieves high transmittance of the ZnSe substrate film in the 2-5.5μm band, and meets the performance requirements of various environmental conditions such as blisters, salt spray, adhesive force, moderate friction, constant temperature and humidity, low temperature and high temperature.
Smart Images

Figure CN119471868A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of infrared optical film technology, and more specifically to a design method and a preparation method of a 2-5.5 μm high-transmittance film on a ZnSe substrate. Background Art
[0002] 2-5.5μm is a common application band for infrared mid-wave. ZnSe substrate anti-reflection films in this band are widely used in infrared temperature measurement, thermal imaging, uncooled infrared focal plane detection, wafer packaging windows and other fields due to their advantages such as low reflection loss, strong signal strength and sensitive detection response. In addition, different application ends have high requirements for the durability of the film, such as film pulling test, friction resistance, constant temperature and humidity resistance, etc. Therefore, it is more difficult to select coating materials, design film systems and improve the specific process of coating technology. Summary of the invention
[0003] In view of the problems existing in the background technology, an object of the present disclosure is to provide a design method and a preparation method for a 2-5.5μm high-transmittance thin film on a ZnSe substrate, which can design and prepare a ZnSe substrate together with the films on both sides to achieve the required transmittance in the 2-5.5μm band.
[0004] Another object of the present disclosure is to provide a design method and a preparation method for a 2-5.5 μm high-transmittance thin film on a ZnSe substrate, which can enable the designed and prepared ZnSe substrate and the film systems on both sides to meet the requirements of different application ends.
[0005] Thus, a design method for a ZnSe substrate 2-5.5μm high-transmittance thin film includes the following steps: Sa, the film system design uses 550nm as the reference wavelength for optical film design, and uses the film stack formula: Sub / 0.6(LHL)^2MK / AIR, the same film system is plated on both sides of Sub, wherein Sub is a ZnSe substrate, AIR represents air, and in the film stack expression: H represents a high-refractive index material ZnSe (zinc selenide) with a thickness of 1 / 4 wavelength, L represents a low-refractive index material YbF3 (ytterbium fluoride) with a thickness of 1 / 4 wavelength, and K represents a 1 / 4 wavelength thickness. The protective layer material is Al2O3 (aluminum oxide), M represents the connecting layer material Y2O3 (yttrium oxide) with a thickness of 1 / 4 wavelength; Sb, through the input film stack formula, generates the film structure of Sub / YbF3 / ZnSe / YbF3 / ZnSe / YbF3 / Y2O3 / Al2O3 / Air; Sc, optimizes the film thickness through thin film design software to obtain the optimal film thickness, and the optimized film structure achieves the target transmittance in the 2-5.5μm band; Sd, inputs the optimized optimal film thickness into the control computer of the coating machine.
[0006] A method for preparing a ZnSe substrate 2-5.5 μm high-transmittance film comprises the following steps: S1, cleaning a ZnSe substrate product as a lens and a co-plating sheet before plating, and preparing four film materials of YbF3, ZnSe, Y2O3 and Al2O3; S2, configuring the coating process conditions and process files, wherein the coating process conditions and process files include coating temperature, background vacuum before plating, film thickness, film material evaporation mode, film material deposition rate, use and parameters of ion source assisted deposition, wherein the film thickness is based on the above-mentioned ZnSe substrate 2-5.5 μm high-transmittance film. The thin film design method described in the optimal film thickness stored in the control computer of the coating machine; S3, the cleaned lens is placed in a fixture, the fixture with the lens is hung in the cavity of the coating machine, and the door is closed for vacuum heating; S4, the film material is pre-melted; S5, the ion source is cleaned; S6, layer coating and monitoring, the film layer is coated on the first side of the lens according to the coating process conditions of step S2 and the configuration of the process file; S7, constant temperature is maintained after coating; S8, cooling and taking out the parts; S9, repeating steps S1 to S8, and coating the second side of the lens.
[0007] The beneficial effects of the present disclosure are as follows.
[0008] In the design method of the ZnSe substrate 2-5.5μm high-transmittance film according to the present disclosure, ZnSe is used as a high-refractive-index material, YbF3 is used as a low-refractive-index material and as a base layer, Y2O3 is used as the final connecting layer, and Al2O3 is used as a protective layer. Therefore, not only can the transmittance of the designed film structure in the 2-5.5μm band meet the requirements, but also the blister test, salt spray test, adhesion test, moderate friction test, constant temperature and humidity test, low temperature test, and high temperature test during the testing process of the film system on both sides are taken into consideration, thereby meeting the requirements of different application ends.
[0009] In the method for preparing a ZnSe substrate 2-5.5μm high-transmittance film according to the present disclosure, based on steps S1 to S9 and based on the optimal film thickness stored in the control computer of the coating machine in the aforementioned design method of a ZnSe substrate 2-5.5μm high-transmittance film, as verified by the test, the transmittance of the prepared ZnSe substrate together with the film systems on both sides in the 2-5.5μm band can meet the requirements, and at the same time can meet the requirements of blister test, salt spray test, adhesion test, moderate friction test, constant temperature and humidity test, low temperature test and high temperature test, thereby meeting the requirements of different application ends. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 It is a schematic structural diagram of the film layer structure according to the design method and preparation method of the ZnSe substrate 2-5.5μm high-transmittance film disclosed in the present invention.
[0011] Figure 2 This is a transmittance curve diagram designed by the design method of the ZnSe substrate 2-5.5μm high-transmittance thin film in Example 1.
[0012] Figure 3 It is a transmittance curve diagram of the accompanying coating sheet and the film system on both sides after the coating is completed in the preparation method of the ZnSe substrate 2-5.5μm high-transmittance thin film of Example 1.
[0013] Figure 4 The following are photos of the preparation method of the ZnSe substrate 2-5.5 μm high-transmittance thin film in Example 1, after the coating is completed, of the accompanying coating sheet and the films on both sides before and after the adhesion test.
[0014] Figure 5 The following are photos of the preparation method of the ZnSe substrate 2-5.5 μm high-transmittance thin film in Example 1, after the coating is completed, of the accompanying coating sheet together with the films on both sides before and after the bubble test. DETAILED DESCRIPTION
[0015] It is understood that the disclosed embodiments are merely examples of the present disclosure, which may be implemented in various forms, and therefore, the specific details disclosed herein should not be interpreted as limiting, but merely as a basis for the claims and as a representative basis for teaching one of ordinary skill in the art to variously implement the present disclosure.
[0016] [Design method of 2-5.5μm high-transmittance thin film on ZnSe substrate]
[0017] Reference Figure 1 and Figure 2 According to the disclosed ZnSe substrate 2-5.5 μm high-transmittance thin film design method, the steps include:
[0018] Sa, the film system design uses 550nm as the reference wavelength for optical thin film design, and uses the film stack formula: Sub / 0.6(LHL)^2MK / AIR. The same film system is plated on both sides of Sub, where Sub is the ZnSe substrate and AIR represents air. In the film stack expression:
[0019] H represents the high refractive index material ZnSe (zinc selenide) with a thickness of 1 / 4 wavelength
[0020] L represents the low refractive index material YbF3 (ytterbium fluoride) with a thickness of 1 / 4 wavelength.
[0021] K represents the protective layer material Al2O3 (aluminum oxide) with a thickness of 1 / 4 wavelength.
[0022] M represents the connecting layer material Y2O3 (yttrium oxide) with a thickness of 1 / 4 wavelength.
[0023] Sb, through the input film stack formula, generates the film layer structure of Sub / YbF3 / ZnSe / YbF3 / ZnSe / YbF3 / Y2O3 / Al2O3 / Air;
[0024] Sc, the film thickness is optimized by thin film design software to obtain the best film thickness. The transmittance of the optimized film structure in the 2-5.5μm band reaches the target;
[0025] Sd, input the optimized best film thickness into the control computer of the coating machine.
[0026] In the design method of the ZnSe substrate 2-5.5μm high-transmittance film according to the present disclosure, ZnSe is used as a high-refractive-index material, YbF3 is used as a low-refractive-index material and as a base layer, Y2O3 is used as the final connecting layer, and Al2O3 is used as a protective layer. Therefore, not only can the transmittance of the designed film structure in the 2-5.5μm band meet the requirements, but also the blister test, salt spray test, adhesion test, moderate friction test, constant temperature and humidity test, low temperature test, and high temperature test in the later-described test process of the film system on both sides are taken into consideration, thereby meeting the requirements of different application ends.
[0027] In one example, in step Sc, for each of the two sides of the lens, the optimal film thickness is expressed as a film structure as follows:
[0028] Sub / YbF3(38.73) / ZnSe(214.84) / YbF3(150.86) / ZnSe(108.41) / YbF3(520.68) / Y2O3(15) / Al2O3(30) / Air. The numbers in brackets are the film thickness. The unit of the film thickness is nm.
[0029] In one example, in step Sc, the average transmittance of the optimized ZnSe substrate in the 2-5.5 μm band is greater than 98%.
[0030] In one example, in step Sa to step Sd, the design software is TFCalc or Essential Macleod.
[0031] [Preparation method of 2-5.5μm high-transmittance thin film on ZnSe substrate]
[0032] The method for preparing a 2-5.5 μm high-transmittance thin film on a ZnSe substrate disclosed in the present invention comprises the following steps:
[0033] S1, cleaning of the ZnSe substrate product and accompanying plating sheet used as lens before plating, and preparation of four kinds of film materials: YbF3, ZnSe, Y2O3 and Al2O3;
[0034] S2, configuration of coating process conditions and process files, including coating temperature, background vacuum before coating, film thickness, film material evaporation mode, film material deposition rate, use and parameters of ion source assisted deposition, wherein the film thickness is based on the optimal film thickness stored in the control computer of the coating machine according to the design method of the ZnSe substrate 2-5.5μm high-transmittance film described above;
[0035] S3, the cleaned lens is placed in a fixture, the fixture with the lens is hung in the cavity of the coating machine, and the door is closed to evacuate and heat;
[0036] S4, pre-melting of film material;
[0037] S5, ion source cleaning;
[0038] S6, layer coating and monitoring, coating the first surface of the lens with a film according to the coating process conditions and configuration of the process file of step S2;
[0039] S7, constant temperature maintenance after coating;
[0040] S8, cooling and picking up;
[0041] S9, repeating steps S1 to S8 to perform film coating on the second surface of the lens.
[0042] In the method for preparing a ZnSe substrate 2-5.5μm high-transmittance film according to the present disclosure, based on steps S1 to S9 and based on the optimal film thickness stored in the control computer of the coating machine in the aforementioned design method of a ZnSe substrate 2-5.5μm high-transmittance film, as verified by subsequent tests, the transmittance of the prepared ZnSe substrate together with the film systems on both sides in the 2-5.5μm band can meet the requirements, and at the same time can meet the requirements of blister test, salt spray test, adhesion test, moderate friction test, constant temperature and humidity test, low temperature test and high temperature test, thereby meeting the requirements of different application ends.
[0043] In one example, in step S1, the product is a (50±0.1) mm×(10±0.1) mm wafer, and the accompanying plating wafer is a (25±0.1) mm×(2±0.1) mm wafer.
[0044] The cleaning in step S1 makes the surface of the lens clean, which is conducive to the adhesion and bonding of the film layer. In one example, the lens is polished with aluminum oxide polishing liquid and then cleaned with ultrasonic pure water. Specifically, the aluminum oxide polishing liquid uses a 0.1 μm polycrystalline diamond liquid produced by Nanjing Henry Precision Optics Co., Ltd.
[0045] In one example, in step S2, the coating temperature is 150°C; the background vacuum before coating is 1.5×10-3 Pa; the film thickness in the configuration of the coating process conditions and process files is based on the optimal film thickness stored in the control computer of the coating machine in the design method of the aforementioned ZnSe substrate 2-5.5μm high-transmittance film; the evaporation mode of the film material is: ZnSe and YbF3 are evaporated by resistance heating, and Y2O3 and Al2O3 are evaporated by electron beam heating; the deposition rate of the film material is: the deposition rate of the ZnSe film layer is The deposition rate of the YbF3 film is The deposition rate of the Y2O3 film is The deposition rate of Al2O3 film is The use of ion source assisted deposition is: all film layers are turned on by ion source. The role of the ion source in ion source assisted deposition is to compact the film layer and reduce the internal stress of the film layer. Specifically, in step S2, ion source assisted deposition uses an APS ion source, and the parameters of the APS ion source are: the ion source voltage is 700±50V, the ion source current is 700±50mA, the acceleration voltage is 500±50V, the acceleration current is 700±50mA, the ion source uses pure argon gas, the ion source argon gas intake is 60±5sccm, and the neutralizer argon gas intake is 8±0.13sccm.
[0046] In one example, in step S2, the coating machine is the Opto-OTFC1300.
[0047] In one example, in step S3, the vacuum is first evacuated to 5×10 -2 Pa, then the cavity of the coating machine starts heating to 150±5℃ and then maintains it for 40min.
[0048] In step S4, the film material is pre-melted to release air and remove impurities to ensure the purity of the film material. In one example, in step S4, when the vacuum reaches (5.0-3.0)×10 -3 At Pa, all the film materials ZnSe, YbF3, Y2O3 and Al2O3 are pre-melted. After the pre-melting of the film materials is completed, the temperature of the cavity of the coating machine reaches 150±5℃ and is kept constant for 10 minutes. Specifically, in step S4, the pre-melting treatment adopts two methods: electron beam heating and resistance heating. For ZnSe film material, the current of resistance heating is 720-760mA; for YbF3 film material, the current of resistance heating is 860-900mA. For Y2O3 film material, the current of electron beam heating is 150-210mA; for Al2O3 film material, the current of electron beam heating is 260-290mA.
[0049] The ion source cleaning in step S5 uses ion bombardment to remove the oxide layer and impurities on the surface of the wafer, making the surface cleaner and increasing the adhesion of the film. In one example, in step S5, the vacuum is drawn to make the vacuum degree of the chamber reach (1.5±0.1)×10 -3 Pa, start the ion source to clean the lens with ions, the ion source is an APS ion source, the parameters of the APS ion source are: ion source voltage is 700±50V, ion source current is 700±50mA, acceleration voltage is 500±50V, acceleration current is 700±50mA, the ion source uses pure argon gas, the ion source argon gas input is 60±5sccm, the neutralizer argon gas input is 8±0.13sccm, and the cleaning time is 60s.
[0050] In one example, in step S6, when coating each film layer, no gas is introduced into the cavity of the coating machine from outside the coating machine, and the cavity of the coating machine is evacuated and the coating temperature is maintained at 150±5°C; each film layer is coated at a cavity temperature of 150°C of the coating machine; the crystal oscillator method is used to monitor the film thickness using the corresponding crystal oscillator of the multiple crystal oscillators of the crystal controller, and after the ion source is cleaned, the crystal controller controls the corresponding operation of the new crystal oscillator among the multiple crystal oscillators, and the crystal oscillator frequency is not less than 5850Hz.
[0051] In one example, in step S7 , the chamber is kept at 150° C. for 30 minutes after plating is completed.
[0052] In one example, in step S8, after step S7 is completed, the temperature is first lowered to 120°C at 1°C / min and held for 5 minutes, then lowered to 90°C at 1°C / min and held for 5 minutes, and then lowered to below 60°C at 1°C / min, and the door is opened to take out the items.
[0053] [test]
[0054] Example 1
[0055] Part 1: Design method of 2-5.5μm high-transmittance thin film on ZnSe substrate
[0056] The design method of 2-5.5μm high-transmittance thin film on ZnSe substrate adopts the following steps:
[0057] Sa, the film system design uses 550nm as the reference wavelength for optical thin film design. In TFCalc, the film stack formula is used: Sub / 0.6(LHL)^2MK / AIR. The same film system is plated on both sides of Sub, where Sub is the ZnSe substrate and AIR represents air. In the film stack expression:
[0058] H represents the high refractive index material ZnSe (zinc selenide) with a thickness of 1 / 4 wavelength
[0059] L represents the low refractive index material YbF3 (ytterbium fluoride) with a thickness of 1 / 4 wavelength.
[0060] K represents the protective layer material Al2O3 (aluminum oxide) with a thickness of 1 / 4 wavelength.
[0061] M represents the connecting layer material Y2O3 (yttrium oxide) with a thickness of 1 / 4 wavelength.
[0062] Sb, through the input film stack formula, generates the film layer structure of Sub / YbF3 / ZnSe / YbF3 / ZnSe / YbF3 / Y2O3 / Al2O3 / Air;
[0063] Sc, the film thickness is optimized by thin film design software TFCalc to obtain the best film thickness. The transmittance of the optimized film structure in the 2-5.5μm band reaches the target.
[0064] In step Sc, for each of the two sides of the lens, the optimal film thickness is determined by the film thickness.
[0065] The layer structure is represented as:
[0066] Sub / YbF3(38.73) / ZnSe(214.84) / YbF3(150.86) / ZnSe(108.41) / YbF3(520.
[0067] 68) / Y2O3(15) / Al2O3(30) / Air. The numbers in brackets are the film thickness.
[0068] The bit is nm;
[0069] Sd, the optimized best film thickness is input into the control computer of the coating machine, and the coating machine is Guangchi OTFC1300.
[0070] Part II: Preparation of 2-5.5μm high-transmittance thin films on ZnSe substrates
[0071] The preparation method of 2-5.5μm high-transmittance thin film on ZnSe substrate adopts the following steps:
[0072] S1, cleaning of the ZnSe substrate product and accompanying plating sheet used as the lens before plating, and preparation of four kinds of film materials: YbF3, ZnSe, Y2O3 and Al2O3. The product is a 50mm×10mm round wafer, and the accompanying plating sheet is a 25mm×2mm round wafer. The lens is polished with alumina polishing liquid and then cleaned with ultrasonic pure water. The alumina polishing liquid uses a 0.1μm polycrystalline diamond liquid produced by Nanjing Henry Precision Optics Co., Ltd.;
[0073] S2, configuration of coating process conditions and process files, including coating temperature, background vacuum before coating, film thickness, film material evaporation mode, film material deposition rate, use and parameters of ion source assisted deposition, wherein the film thickness is based on the optimal film thickness stored in the control computer of the coating machine in the design method of ZnSe substrate 2-5.5μm high-transmittance film in the first part,
[0074] In step S2,
[0075] The coating temperature is 150°C;
[0076] The background vacuum before plating is 1.5×10 -3 Pa;
[0077] The film thickness in the configuration of the coating process conditions and process files is based on the optimal film thickness stored in the control computer of the coating machine as described in the design method of the ZnSe substrate 2-5.5μm high-transmittance film in the first part;
[0078] The evaporation mode of the film materials is: ZnSe and YbF3 are evaporated by resistance heating, Y2O3 and Al2O3 are evaporated by resistance heating,
[0079] Evaporation using electron beam heating;
[0080] The deposition rate of the film material is: The deposition rate of the ZnSe film layer is The deposition rate of the YbF3 film is The deposition rate of the Y2O3 film is The deposition rate of Al2O3 film is
[0081]
[0082] The use of ion source assisted deposition is: all film layers are turned on with ion source;
[0083] The ion source assisted deposition uses an APS ion source. The parameters of the APS ion source are: the ion source voltage is 700V, the ion source current is 700mA, the acceleration voltage is 500V, the acceleration current is 700mA, the ion source uses pure argon gas, the ion source argon gas flow rate is 60sccm, and the neutralizer argon gas flow rate is 8sccm.
[0084] S3, put the cleaned lens into the fixture, hang the fixture with the lens into the chamber of the coating machine, close the door, and first vacuumize to 5×10 -2 Pa, then the coating machine chamber starts heating to 150°C and then maintains it for 40 minutes;
[0085] S4, film material pre-melting, when the vacuum reaches 5.0×10 -3At Pa, all the film materials ZnSe, YbF3, Y2O3 and Al2O3 are pre-melted. After the pre-melting of the film materials is completed, the temperature of the cavity of the coating machine reaches 150℃ and is kept constant for 10 minutes.
[0086] In step S4, the pre-melting process uses electron beam heating and resistance heating.
[0087] For ZnSe film material, the current of resistance heating is 740mA;
[0088] For YbF3 film material, the current of resistance heating is 880mA.
[0089] For Y2O3 film material, the current of electron beam heating is 180mA;
[0090] For Al2O3 film material, the current of electron beam heating is 275mA;
[0091] S5, ion source cleaning, vacuum extraction to make the vacuum degree of the chamber reach 1.5×10 -3 Pa, start the ion source to clean the lens with ions, the ion source is an APS ion source, the parameters of the APS ion source are: ion source voltage is 700V, ion source current is 700mA, acceleration voltage is 500V, acceleration current is 700mA, the ion source uses pure argon gas, the ion source argon gas flow rate is 60sccm, the neutralizer argon gas flow rate is 8sccm, and the cleaning time is 60s;
[0092] S6, layer coating and monitoring, coating the first surface of the lens with a film according to the coating process conditions and process file configuration of step S2,
[0093] In step S6,
[0094] When coating each film layer, no gas is introduced from outside the coating machine into the coating machine cavity, and the coating machine cavity is kept evacuated and the coating temperature is kept at 150°C;
[0095] Each film layer is coated at a chamber temperature of 150°C in the coating machine;
[0096] The crystal oscillator method uses the corresponding crystal oscillator of the multiple crystal oscillators of the crystal controller to monitor the film thickness. After the ion source is cleaned, the crystal controller controls the corresponding operation of the new crystal oscillator among the multiple crystal oscillators.
[0097] The vibration frequency is 5990Hz;
[0098] S7, after plating is completed, the cavity is kept at 150°C for 30 minutes;
[0099] S8, after step S7 is completed, first cool down to 120°C at 1°C / min and hold for 5 minutes, then cool down to 90°C at 1°C / min and hold for 5 minutes, then cool down to 60°C at 1°C / min, and open the door to take out the items;
[0100] S9, repeating steps S1 to S8 to perform film coating on the second surface of the lens.
[0101] Comparative Example 1
[0102] Except that in step S5 the ion source voltage is 500 V, the ion source current is 500 mA, and the acceleration current is 300 mA, the rest is the same as in Example 1.
[0103] Comparative Example 2
[0104] Except that in step S5 the ion source uses a mixture of argon and oxygen, the flow rate of argon into the ion source is 10 sccm, and the flow rate of oxygen into the ion source is 50 sccm, the rest is the same as in Example 1.
[0105] Comparative Example 3
[0106] Except that the deposition rate of the Al2O3 film in step S2 is Other than that, the same as in Example 1.
[0107] Comparative Example 4
[0108] In addition to using IDA (the film material of the IDA film layer is Ida (Ti-Pr-Oxide) particles with a diameter of 0.7-3.5 mm and a grade of 0484519 purchased from Umicore, USA) to replace Y2O3 in steps S1, S2 and S4, and using electron beam heating evaporation for IDA in step S2, the deposition rate of the IDA film layer is In step S4, except that the current of electron beam heating of the IDA film material is 450 mA, the rest is the same as in Example 1.
[0109] Comparative Example 5
[0110] Except that YbF3 is used to replace Al2O3 in step S1, step S2 and step S4, the rest is the same as in Example 1.
[0111] Figure 2 This is a transmittance curve designed by the design method of the ZnSe substrate 2-5.5μm high transmittance film in Example 1. Figure 2 The average transmittance of the ZnSe substrate and the films on both sides in the 2-5.5μm band is 98.5%
[0112] Figure 3This is a transmittance curve of the accompanying plate and the film system on both sides after the coating is completed in the preparation method of the ZnSe substrate 2-5.5μm high-transmittance film of Example 1. Figure 3 The average transmittance of the accompanying coating sheet and the film system on both sides is 97.2%.
[0113] The accompanying plating sheets of Example 1 and Comparative Examples 1-5 together with the film systems on both sides were subjected to the following overall performance test.
[0114] Water bubble test: Take tap water to conduct a water bubble test for 2 hours to observe whether the film layer on each surface falls off or cracks.
[0115] Salt spray test: neutral salt spray test for 24 hours, observe whether the film layer on each surface falls off or cracks.
[0116] Adhesion test: Use your hands to stick 3M tape on each side and pull the tape in the direction opposite to the sticking end to see if the film layer is pulled up.
[0117] Moderate friction test: The film layer is rubbed 50 times with a rubber friction head wrapped with degreased cloth at a pressure of 4.9N, and observe whether there are scratches or damage.
[0118] Constant temperature and humidity test: In a constant temperature and humidity chamber, at 50°C and 95% relative humidity for 24 hours, observe whether the film layers on each surface fall off or crack.
[0119] Low temperature test: In a low temperature box, at -40℃ for 24 hours, observe whether the film layers on each surface fall off or crack.
[0120] High temperature test: In a high temperature box, 85℃ for 24 hours, observe whether the film layers on each surface fall off or crack.
[0121] Figure 4 These are photos of the accompanying plated sheet before and after the adhesion test after the coating was completed in the preparation method of the ZnSe substrate 2-5.5 μm high-transmittance thin film of Example 1.
[0122] Figure 5 These are photos of the preparation method of the ZnSe substrate 2-5.5 μm high-transmittance thin film in Example 1, after the coating is completed, of the accompanying coating sheet together with the film systems on both sides before and after the water bubble test.
[0123] Table 1 shows the average transmittance of Example 1 and Comparative Examples 1-5 and the results of various tests
[0124] Table 1 Average transmittance of Example 1 and Comparative Examples 1-5 and results of various tests
[0125]
[0126] The above detailed description is used to describe multiple exemplary embodiments, but this document is not intended to be limited to the explicitly disclosed combinations. Therefore, unless otherwise stated, the various features disclosed herein can be combined together to form multiple additional combinations that are not shown for the sake of simplicity.
Claims
1. A design method for a 2-5.5 μm high-transmittance thin film on a ZnSe substrate, characterized in that: Includes steps: Sa, the film system design uses 550nm as the reference wavelength for optical thin film design, and uses the film stack formula: Sub / 0.6(LHL)^2MK / AIR. The same film system is plated on both sides of Sub, where Sub is the ZnSe substrate and AIR represents air. In the film stack expression: H represents the high refractive index material ZnSe (zinc selenide) with a thickness of 1 / 4 wavelength L represents the low refractive index material YbF3 (ytterbium fluoride) with a thickness of 1 / 4 wavelength. K represents the protective layer material Al2O3 (aluminum oxide) with a thickness of 1 / 4 wavelength. M represents the connection layer material Y2O3 (yttrium oxide) with a thickness of 1 / 4 wavelength. Sb, through the input film stack formula, generates the film layer structure of Sub / YbF3 / ZnSe / YbF3 / ZnSe / YbF3 / Y2O3 / Al2O3 / Air; Sc, the film thickness is optimized by thin film design software to obtain the best film thickness. The transmittance of the optimized film structure in the 2-5.5μm band reaches the target; Sd, input the optimized best film thickness into the control computer of the coating machine.
2. The design method of the ZnSe substrate 2-5.5 μm high-transmittance thin film according to claim 1, characterized in that: In step Sc, for each of the two sides of the lens, the optimal film thickness is expressed as a film structure: Sub / YbF3(38.73) / ZnSe(214.84) / YbF3(150.86) / ZnSe(108.41) / YbF3(520.68) / Y2O3(15) / Al2O3(30) / Air, the numbers in brackets are the film thickness, and the unit of the film thickness is nm; In step Sc, the average transmittance of the optimized ZnSe substrate in the 2-5.5 μm band is greater than 98%.
3. A method for preparing a 2-5.5 μm high-transmittance thin film on a ZnSe substrate, characterized in that: Includes steps: S1, cleaning of the ZnSe substrate product and accompanying plating sheet used as lens before plating, and preparation of four kinds of film materials: YbF3, ZnSe, Y2O3 and Al2O3; S2, configuration of coating process conditions and process files, the configuration of coating process conditions and process files includes coating temperature, background vacuum before coating, film thickness, evaporation mode of film material, deposition rate of film material, use and parameters of ion source assisted deposition, wherein the film thickness is based on the optimal film thickness stored in the control computer of the coating machine according to any one of claims 1-2; S3, the cleaned lens is placed in a fixture, the fixture with the lens is hung in the cavity of the coating machine, and the door is closed to evacuate and heat; S4, pre-melting of film material; S5, ion source cleaning; S6, layer coating and monitoring, coating the first surface of the lens with a film according to the coating process conditions and configuration of the process file of step S2; S7, constant temperature maintenance after coating; S8, cooling and picking up; S9, repeating steps S1 to S8 to perform film coating on the second surface of the lens.
4. The method for preparing a 2-5.5 μm high-transmittance thin film on a ZnSe substrate according to claim 3, characterized in that: In step S1, The product is a (50±0.1)mm×(10±0.1)mm round disc, and the accompanying plating sheet is a (25±0.1)mm×(2±0.1)mm round disc; The lenses are polished with aluminum oxide polishing liquid and then cleaned with ultrasonic pure water; The alumina polishing liquid adopts the 0.1μm polycrystalline diamond liquid produced by Nanjing Henry Precision Optics Co., Ltd.
5. The method for preparing a 2-5.5 μm high-transmittance thin film on a ZnSe substrate according to claim 3, characterized in that: In step S2, The coating temperature is 150°C; The background vacuum before plating is 1.5×10 -3 Pa; The coating process conditions and the film thickness in the configuration of the process file are based on The optimum film thickness stored in the control computer of the coating machine according to claim 2; The evaporation mode of the film materials is: ZnSe and YbF3 are evaporated by resistance heating, and Y2O3 and Al2O3 are evaporated by electron beam heating; The deposition rate of the film material is: The deposition rate of the ZnSe film layer is The deposition rate of the YbF3 film is The deposition rate of the Y2O3 film is The deposition rate of Al2O3 film is The use of ion source assisted deposition is: all film layers are turned on with ion source; The ion source assisted deposition uses an APS ion source. The parameters of the APS ion source are: ion source voltage is 700±50V, ion source current is 700±50mA, acceleration voltage is 500±50V, acceleration current is 700±50mA, the ion source uses pure argon gas, the ion source argon gas flow rate is 60±5sccm, and the neutralizer argon gas flow rate is 8±0.13sccm; The coating machine is Guangchi OTFC1300.
6. The method for preparing a 2-5.5 μm high-transmittance thin film on a ZnSe substrate according to claim 3, characterized in that: In step S3, the vacuum is first evacuated to 5×10 -2 Pa, then the cavity of the coating machine starts heating to 150±5℃ and then maintains it for 40min.
7. The method for preparing a 2-5.5 μm high-transmittance thin film on a ZnSe substrate according to claim 3, characterized in that: In step S4, when the vacuum reaches (5.0-3.0)×10 -3 At Pa, all the film materials ZnSe, YbF3, Y2O3 and Al2O3 are pre-melted. After the pre-melting of the film materials is completed, the temperature of the cavity of the coating machine reaches 150±5℃ and is kept constant for 10 minutes; In step S4, the pre-melting process uses electron beam heating and resistance heating. For ZnSe film material, the current of resistance heating is 720-760mA; For YbF3 film material, the current of resistance heating is 860-900mA. For Y2O3 film material, the current of electron beam heating is 150-210mA; For Al2O3 film material, the current of electron beam heating is 260-290mA.
8. The method for preparing a 2-5.5 μm high-transmittance thin film on a ZnSe substrate according to claim 3, characterized in that: In step S5, the vacuum is drawn to make the vacuum degree of the cavity reach (1.5±0.1)×10 -3 Pa, start the ion source to clean the lens with ions, the ion source is an APS ion source, the parameters of the APS ion source are: ion source voltage is 700±50V, ion source current is 700±50mA, acceleration voltage is 500±50V, acceleration current is 700±50mA, the ion source uses pure argon gas, the ion source argon gas input is 60±5sccm, the neutralizer argon gas input is 8±0.13scc, and the cleaning time is 60s.
9. The method for preparing a 2-5.5 μm high-transmittance thin film on a ZnSe substrate according to claim 3, characterized in that: In step S6, When coating each film layer, do not introduce any gas from outside the coating machine into the coating machine cavity and keep the coating machine cavity evacuated and the coating temperature maintained at 150±5℃; Each film layer is coated at a chamber temperature of 150°C in the coating machine; The crystal oscillator method is used to monitor the film thickness using the corresponding crystal oscillator pieces of the multiple crystal oscillator pieces of the crystal controller. After the ion source is cleaned, the crystal controller controls the corresponding operation of the new crystal oscillator pieces among the multiple crystal oscillator pieces, and the crystal oscillator frequency is not less than 5850Hz.
10. The method for preparing a 2-5.5 μm high-transmittance thin film on a ZnSe substrate according to claim 3, characterized in that: In step S7, after the plating is completed, the cavity is kept at 150° C. for 30 minutes; In step S8, after step S7 is completed, the temperature is first lowered to 120°C at 1°C / min and held for 5 minutes, then lowered to 90°C at 1°C / min and held for 5 minutes, and then lowered to below 60°C at 1°C / min, and the door is opened to take out the items.
Citation Information
Patent Citations
Visible light and mid-infrared double-spectrum channel thin film device and preparation method thereof
CN116469900A
Preparation method for plating double-waveband antireflection film on zinc selenide substrate
CN117448751A
Preparation method for plating two-waveband film system on calcium fluoride substrate
CN118291920A
IR neutral filter with a substrate transparent for infra-red radiation
EP2381280A1
Cited By
Low phase difference metal reflector suitable for space environment and preparation method and application thereof
CN122018064A